Alcohol Consumption Practices among Married Women of Reproductive Age in Nepal: A Population Based Household Survey - Thapa, Narbada; Aryal, Krishna Kumar; Puri, Rupendra; Shrestha, Saraswoti; Shrestha, Sheela; Thapa, Pukar; Mehata, Suresh; Thapa, Pushpa; Banjara, Megha Raj; Stray-Pedersen, Babill (PLOS ONE, 2016)
Background Alcohol chemically known as ethanol, causes several health, economic and social consequences across the world. Literatures suggest potential harm of alcohol drinking by pregnant women especially to the fetus and the mother. Despite anumber of significant public health problems related to alcohol consumption, this area has been ignored in Nepal and information at the national level is limited. Thus this study aimed at finding the prevalence of alcohol consumption among married women of reproductive age. Methods A nationally representative household survey was carried out from April to August 2013 by taking 16 districts across all 15 eco administrative regions. From the selected districts, 86 village development committees and 14 municipalities were selected as primary sampling units using probability proportionate to size, followed by random selection of 3 wards from each primary sampling unit. Finally, 30 households within each ward were selected using systematic random sampling, and one married women of reproductive age from each household. A total of 9000 married women of reproductive age were interviewed using a semi-structured questionnaire, on alcohol consumption practices including environmental factors and socio demographic characteristics and were included in the analysis. Results National prevalence of alcohol consumption ever among married women of reproductive age was 24.7% (95% CI:21.7–28.0), last 12 months 17.9% (95% CI:15.3–20.7) and last 30 days (current drinking) 11.8% (95% CI:9.8–14.1). There was substantial variation among the districts ranging from 2% to 60%. Multivariable analysis suggests women with no education or within formal education, dalit and janajatis ethnicity, whose husbands drink alcohol, who brew alcohol at home and women from mountains were significantly at higher risk of consuming alcohol. Among the women who drank alcohol in last 12 months, a substantial proportion of them drank home brewed alcoholic beverages (95.9%, 95% CI:94.3–97.4). Conclusion Alcohol consumption was common practice among married women of reproductive age in Nepal with variation among the subgroups of population. Thus, further investigation and behavior change communication interventions to reduce alcohol consumption especially among the women with higher risk of drinking is essential.